The good-wholesome life (hayātan tayyibah) as an Islamic lifestyle standard - Ali, Mohammed Farid (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2014)
In one respect the contemporary lifestyle of Muslims is essentially no different from the lifestyle of other individuals. For both Muslims and non-Muslims, the optimum standards of the good life require a sufficient amount of material means for possession and use. It is natural and necessary to possess sufficient material means in order to fulfil our human needs. This only becomes problematic when material possessions begin to stimulate appetites and incite a never ending thirst for more possessions beyond what is sufficient. This material based standard can replace human values by material ones. Human values then become measured according to price-tags and brand-names reflecting wordly criteria of fulfilment. When such standards are taken for granted, materials are acquired not merely to fulfil necessary human needs, but for servicing appetites beyond the healthy bounds of moderation and a balanced existence. How may we assess what is natural and necessary for proper human standards? The idea of the ‘goodwholesome life (Ḥayātan Ṭayyibah)’ stated in the Qur’an (al-Naḥl 16:97) offers an altogether different standard. This viewpoint explores the meaning of this phrase in various tafsīr works and seeks to establish the Qur’anic basis for an Islamic standard of an ideal human lifestyle.